The Relationship Between Self-Esteem, Emotional Intelligence, and Empathy Among Students From Six Health Professional Programs. Issue 5 (20th October 2019) - Sa, Bidyadhar; Ojeh, Nkemcho; Majumder, Md Anwarul Azim; Nunes, Paula; Williams, Stella; Rao, Suresh Rangoji; Youssef, Farid F.
Abstract: Theory: Psychosocial skills such as communication, empathy, and emotional intelligence are now considered key attributes of health professionals. Self-esteem is another important construct that is less well studied. Self-esteem is important because low levels have been linked to depression, suicide, and eating disorders. Given that health professional students experience high levels of stress and are at increased risk for similar psychopathology, self-esteem may be an important variable in student well-being and performance after graduation. Hypotheses: This study sought to explore self-esteem during students' 1st year of training hypothesizing that several would demonstrate low self-esteem. It is also hypothesized that emotional intelligence and empathy would be associated with self-esteem. Method: A cross-sectional survey was conducted, and data were gathered from dental, medical, nursing, optometry, pharmacy and veterinary students. Self-report questionnaires assessing self-esteem, emotional intelligence, and empathy were completed and demographic information was collected. Scores were calculated and differences between groups analyzed with analysis of variance and chi-square testing. Pearson's correlation was used to assess associations between the constructs. Results: The mean self-esteem score was 26.2 ± 2.3 but 21% of the sample evidenced low self-esteem. There was no difference in the proportion of students demonstrating low self-esteem among programs. Gender did not have a significant effect on self-esteem scores, though ethnicity did. Emotional intelligence scores were higher among male individuals than among female. Emotional intelligence and empathy showed a small association with self-esteem. Conclusions: A significant proportion of health professional students suffer from low self-esteem during their 1st year of study. Such students may be more susceptible to the stresses associated with study and the development of psychopathology. More research needs to be conducted to explore the relationships between self-esteem, emotional intelligence, and empathy with a view to strengthening training in these areas and managing the challenges faced by health professional students.